CD56neg CD16+ cells represent a distinct mature NK cell subset with altered phenotype and are associated with adverse clinical outcome upon expansion in AML - Wlosik, Julia; Orlanducci, Florence; Richaud, Manon; Demerle, Clemence; Amara, Amira Ben; Rouviere, Marie-Sarah; Livrati, Philippe; Gorvel, Laurent; Hospital, Marie-Anne; Dulphy, Nicolas; Devillier, Raynier; Vey, Norbert; et al. (Frontiers in Immunology, 2025)
IntroductionAcute myeloid leukemia (AML) is a rare haematological cancer with poor 5-years overall survival (OS) and high relapse rate. Leukemic cells are sensitive to Natural Killer (NK) cell mediated killing. However, NK cells are highly impaired in AML, which promote AML immune escape from NK cell immune surveillance. We made the first report of CD56neg CD16+ NK cells expansion in AML. This unconventional subset has been reported to expand in some chronic viral infections. Although it is unclear whether CD56neg NK cells expansion mechanism is common across diseases, it seems more relevant than ever to further investigate this subset, representing a potential therapeutic target.MethodsWe used PBMCs from AML patients and HV to perform mass cytometry, spectral flow cytometry, bulk RNA-seq and in vitro assays in order to better characterize CD56neg CD16+ NK cells that expand in AML.ResultsWe confirmed that CD56neg CD16+ NK cells represent a unique NK cell subset coexpressing Eomes and T-bet. CD56neg CD16+ NK cells could recover CD56 expression in vitro where they displayed unaltered NK cell functions. We previously demonstrated that CD56neg CD16+ NK cells expansion at diagnosis was associated with adverse clinical outcome in AML. Here, we validated our findings in a validation cohort of N=38 AML patients. AML patients with CD56neg CD16+ NK cells expansion at diagnosis had decreased overall survival (HR[CI95]=5.5[1.2-24.5], p=0.0251) and relapse-free survival (HR[CI95]=13.1[1.9-87.5], p=0.0079) compared to AML patients without expansion after 36 months follow-up. RNA-seq unveiled that CD56neg CD16+ NK cells were mature circulating NK cells with functional capacities. Upon expansion, CD56neg CD16+ NK cells from AML patients showed altered proteomic phenotype, with increased frequency of terminally mature CD56neg CD16+ NK cells expressing TIGIT along with decreased frequency of Siglec-7+ CD56neg CD16+ NK cells.DiscussionTaken together, our results suggest that we could harness CD56neg CD16+ NK cells cytotoxic potential in vitro to restore NK cell anti-tumor response in AML patients with CD56neg CD16+ NK cells expansion and improve patients’ prognosis. To conclude, CD56neg CD16+ NK cells represent a relevant target for future NK-cell-based immunotherapies in AML.